Uncovering Guests’ Satisfaction and Dissatisfaction Through Tripadvisor Reviews: Evidence From Sheraton Senggigi Beach Resort - Sukmana, Febrian Humaidi; Maryanti, Sri (SENTRALISASI, 2025)
This study examines key factors influencing guest satisfaction and dissatisfaction at Sheraton Senggigi Beach Resort (SSBR) based on online reviews, comparing high-rated (5-Star and 4-Star) and low-rated (3-Star, 2-Star, and 1-Star) reviews to identify aspects driving positive and negative guest perceptions. A content analysis was conducted on 1,921 English-language reviews from TripAdvisor spanning 2005 to 2024, with thematic analysis employed to uncover patterns in guest experiences. The findings reveal that positive reviews emphasize excellent service, well-maintained facilities, strategic location, and cleanliness as primary drivers of satisfaction, whereas negative reviews highlight outdated room conditions, inadequate service, and cleanliness issues as major sources of dissatisfaction. This study offers a unique comparative analysis of guest reviews, contributing to the academic literature by demonstrating how online reviews can be leveraged to understand guest experiences at luxury hotels while addressing gaps in research on rating-based review differences.